Adaptive simplified fuzzy logic controller of unmanned underwater vehicle for depth and pitch control - Seik Heng, Kai (2016)
Fuzzy Logic Controller (FLC) is an intelligent control that completed and performed with inference rules and membership function.Unmanned Underwater Vehicle (UUV) is a submarine-like robot device that can deploy for underwater tasks,such as deep sea survey and rescue operation,repair and maintenance for seabed petroleum gas pipeline.Fuzzy Logic Controller has various efforts and advantages instead of linear controller to control the depth and pitch angle of an UUV due to the ability of FLC to adopt the hydrodynamics w1certainties underwater.However,conventional fuzzy logic controller (CFLC) requires more computational power due to their Multi Input Single Output (MlSO) method,complex processes and decision making that deal with rules based storage,membership function,fuzzi fication and de-fuzzification processes.In this project,an Adaptive Simplified Fuzzy Logic Controller (ASFLC) is proposed for depth and pitch angle control of an UUV,where ASFLC is a controller operate by using Single Input Single Output (SISO) method.ASFLC simplified the rules based storage and reduce the inputs for UUV's depth and pitch angle control parameters.Performance of proposed ASFLC is validated by simulation in Matlab/Simulink.ASFLC ere ated based on the signed distance method,which eventually reduces the controller as a single-input single-output (SlSO)controller. As a result,the rise time and settling time of depth and pitch angle is faster and overshoot of the system is reduced compared to conventional fuzzy logic controller and provides a significant reduction in rules,tuning parameters and a simpler control structure,as compared to the conventional FLC.